PERAN KOMITMEN AFEKTIF DALAM MEMEDIASI LEARNING ORIENTATION DAN MODAL SOSIAL TERHADAP KINERJA SUMBER DAYA MANUSIA - Zaenudin Zaenudin; An Nisa Nuur Prasetyaninghayu (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
This study aims to determine and analyze the influence of learning orientation and social capitalon human resource performance with affective commitment as an intervening variable at PT.SAI Apparel Industries Semarang. Population in this research is all employees of productionof PT. SAI Apparel Industries Semarang as many as 3.100 people, with a sample size of 97respondents. The sampling technique is Proportional Random Sampling. The analytical tool isthe path of analysis, where previously tested the validity and reliability as well as the classicalassumption test.The result showed that learning orientation and social capital proved to havepositive and significant impact on affective commitment and human resource performance.Affective commitment has a positive and significant effect on human resource performance.Affective commitment can be an intervening variable between learning orientation towardshuman resource performance, meaning higher learning orientation, it will increasingly make theemployee able to adjust themselves between the system with the work environment so that it willincrease the affective commitment of employees in achieving maximum performance. Affectivecan be a variable intervening between social capital to human resource performance, it can beinterpreted that the height of social capital, the more the formation of sense of togetherness,solidarity, and also the responsibility of common progress in supporting employees affectivecommitment, which will certainly impact on the high performance of employees maximum.Keywords : Learning orientation, social capital, affective commitment and human resourceperformance